Sistem Informasi Pendataan Potensi Pertanian Kabupaten Kepulauan Talaud Berbasis Web - Widia Nofhita Gumolung; Eliyah Acantha M Sampetoding; Alfret Luasunaung; Yuliyanto Yuliyanto; Esther Sanda Manapa (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Economic development in the agricultural sector is intended to increase farmers' income and to equalize development in rural areas. The agricultural potential data collection information system is carried out to find out the various advantages or privileges that exist in the Talaud Islands Regency. One of the government agencies that carry out this activity is the Department of Food Security and Agriculture of the Talaud Islands Regency. This is the benchmark of this discussion and research. The author's team conducted research at the Department of Food Security and Agriculture of the Talaud Islands Regency by collecting data in the field, the authors used questionnaires and interviews. Interviews were conducted with the head of the plantation sector and one staff member of the plantation sector. Based on the results of research in the field and adapted to the needs of potential data by information users, the authors designed an application of information systems for data collection of agricultural potential in Talaud Islands Regency based on a website This system is made to facilitate potential data collection, access and quick information. Stakeholders in collecting data on agricultural potential in the Talaud Islands Regency can access potential data online without having to deal directly with agricultural potential managers